Pembangkit Listrik Tenaga Surya (PLTS) Off Grid untuk Surau Nur Jannah kawasan wisata Puncak Labuang - Pribadi, Rizki Aditio; Fitriadi, Fitriadi; Asrul, Junaidi; Firmansyah, Firmansyah; Herisajani, Herisajani; Yuhaidizen, Yuhaidizen (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Community service program for lecturers in the Department of Electrical Engineering, in order to fulfill the Tridharma of the Padang State Polytechnic College (PNP) for the 2024 fiscal year. The activity carried out is the installation of an Off Grid Solar Power Plant (PLTS) at Surau Nur Jannah in the Puncak Labuang tourist area Sweet Limau Padang City. Based on the Limau Manis sub-district planning analysis document for the next five years, one of the potentials that will be developed to improve the community's economy is to make the Puncak Labuang area a glamping/camping ground tourism area, farming education with an environmentally friendly concept. Currently, the development of this tourist area is carried out independently by the community by working together, such as building a prayer room. Based on the results of field visits and meetings between the PNP thematic service team and the community, on that occasion the community expressed complaints about limited human resources related to the development of the Puncak Labuang tourist area. Some of the issues raised include graphic design, spatial planning, governance, the need for clean water and the availability of electrical energy. PNP, through its community service activities, helps find solutions to solve problems in the Puncak Labuang tourist area by involving all departments in the PNP so that the Puncak Labuang tourist area can be known and visited by tourists.